2015
DOI: 10.3171/2015.4.peds14667
|View full text |Cite
|
Sign up to set email alerts
|

Opioid overdose in a child: case report and discussion with emphasis on neurosurgical implications

Abstract: In environments in which opioids are increasingly abused for recreation, children are becoming more at risk for both accidental and nonaccidental intoxication. In toxic doses, opioids can cause potentially lethal acute leukoencephalopathy, which has a predilection for the cerebellum in young children. The authors present the case of a 2-year-old girl who suffered an accidental opioid overdose, presenting with altered mental status requiring cardiorespiratory support. She required emergency posterior fossa deco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 34 publications
0
33
0
Order By: Relevance
“…In both instances, patients had good clinical outcomes though with some deficits considering the life-threatening nature of their presentations. To our knowledge, there are only two other reported cases of children requiring surgical posterior fossa decompression for malignant cerebellar edema after accidental prescription opioid ingestion (9, 10). Both cases had nearly identical clinical courses and radiographic findings when compared to our patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In both instances, patients had good clinical outcomes though with some deficits considering the life-threatening nature of their presentations. To our knowledge, there are only two other reported cases of children requiring surgical posterior fossa decompression for malignant cerebellar edema after accidental prescription opioid ingestion (9, 10). Both cases had nearly identical clinical courses and radiographic findings when compared to our patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our comprehensive review of the literature revealed 8 additional cases of acute pediatric opioid-induced leukoencephalopathy with cerebellar edema (Table 1) (9, 10, 2530). Patients were toddlers, who accidentally consumed their caregiver’s prescription opiates orally with the exception of one case in which administration occurred through a transdermal fentanyl patch (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurobehavioral presentations typically include altered mental status, psychomotor changes, depression, anxiety, visuospatial deficit, coma, or death, while language capabilities are characteristically spared [1, 2, 3]. It is important to note that cases of acute TLE may present with sudden increased intracranial pressure, acute hydrocephalus, and herniation due to predominant cerebellar involvement.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Although the exact mechanism of toxicity remains speculative, patterns of injury have been described. Histopathology demonstrates white matter vacuolization and spongiform defects as hallmarks of TLE [1, 2, 3].…”
Section: Introductionmentioning
confidence: 99%